Identification and characterization of reactive metabolites in myristicin-mediated mechanism-based inhibition of CYP1A2. (25th July 2015) - Yang, Ai-Hong; He, Xin; Chen, Jun-Xiu; He, Li-Na; Jin, Chun-Huan; Wang, Li-Li; Zhang, Fang-Liang; An, Li-Jun
Graphical abstract: It is identified that myristicin is a mechanism-based inhibitor of CYP1A2 through CYP cocktail screening, IC50 shift calculation and GSH capturing assays in HLMs. And the reactive metabolites were identified as a quinone and its tautomer through detailed analysis the cleavage processes of metabolites and GSH-myristicin adduct in phase I metabolism assays using UPLC-MS 2 . Highlights: Myristicin has been identified as a mechanism-based inhibitor of CYP1A2. Two metabolites have been identified in phase I and glutathione capturing assays. The reactive metabolites were identified as a quinone and its tautomer. Abstract: Myristicin belongs to the methylenedioxyphenyl or allyl-benzene family of compounds, which are found widely in plants of the Umbelliferae family, such as parsley and carrot. Myristicin is also the major active component in the essential oils of mace and nutmeg. However, this compound can cause adverse reactions, particularly when taken inappropriately or in overdoses. One important source of toxicity of natural products arises from their metabolic biotransformations into reactive metabolites. Myristicin contains a methylenedioxyphenyl substructure, and this specific structural feature may allow compounds to cause a mechanism-based inhibition of cytochrome P450 enzymes and produce reactive metabolites. Therefore, the aim of this work was to identify whether the role of myristicin in CYP enzyme inhibition is mechanism-based inhibition and to gain further information regarding the structure of the resulting reactive metabolites. CYP cocktail assays showed that myristicin most significantly inhibits CYP1A2 among five CYP enzymes (CYP1A2, CYP2D6, CYP2E1, CYP3A4 and CYP2C19) from human liver microsomes. The 3.21-fold IC50 shift value of CYP1A2 indicates that myristicin may be a mechanism-based inhibitor of CYP1A2. Next, reduced glutathione was shown to block the inhibition of CYP1A2, indicating that myristicin utilized a mechanism-based inhibition. Phase I metabolism assays identified two metabolites, 5-allyl-1-methoxy-2, 3-dihydroxybenzene (M1) and 1'-hydroxymyristicin or 2', 3'-epoxy-myristicin (M2). Reduced glutathione capturing assays captured the glutathione-M1 adduct, and the reactive metabolites were identified using UPLC-MS 2 as a quinone and its tautomer. Thus, it was concluded that myristicin is a mechanism-based inhibitor of CYP1A2, and the reactive metabolites are quinone tautomers. Additionally, the cleavage process of the glutathione-M1 adduct was analyzed in further detail. This study provides additional information on the metabolic mechanism of myristicin inhibition and improves risk evaluation for this compound.